Anti-hypoxic Effect of Polysaccharide Extract of Brown Seaweed Sargassum dentifolium in Tongue Squamous Cell Carcinoma - Gamal-Eldeen, Amira M.; Raafat, Bassem M.; Alrehaili, Amani A.; El-Daly, Sherien M.; Hawsawi, Nahed; Banjer, Hamsa J.; Raafat, Eman M.; Almehmadi, Mazen M. (Frontiers in Nutrition, 2022)
Sargassum dentifolium, ‎(Turner) C. Agarth, 1820, is an edible brown alga collected from red ‎seashores, Egypt. Oral tongue squamous cell carcinoma (OTSCC) is an aggressive malignancy. ‎Hypoxia leads to chemotherapeutic resistance. This work aimed to explore the anti-hypoxia effect of ‎water-soluble polysaccharide fractions of S. dentifolium (SD1-SD3), in CAL-27 OTSCC cells. Cell ‎cytotoxicity assay (MTT); cell death mode (DNA staining); total hypoxia (pimonidazole), HIF-1α ‎‎(ELISA and immunocytochemistry), HIF-1β (ELISA), and hsa-miRNA-21-5p and hsa-miRNA-210-3p ‎‎(qRT-PCR) were investigated. SD1 and SD2 showed a cytotoxic effect due to apoptosis. SD2 and ‎SD3 decreased total cell hypoxia, inhibited miR-210 (p<0.001 and p<0.01), miR-21 (p<0.01 and ‎p<0.05), and HIF-1α (p<0.01 and p<0.05), respectively. However, only SD3 suppressed HIF-1β ‎‎(p<0.05). In conclusion, SD2 showed a potential anti-hypoxia effect through amelioration of HIF-1α ‎regulators, which may help in decreasing hypoxia-induced therapeutic resistance‎.‎